A safer, faster, leaner workplace? Technical‐maintenance worker perspectives on digital drone technology 'effects' in the European steel industry. (3rd November 2020) - Stroud, Dean; Weinel, Martin
Abstract : This paper focuses on technical‐maintenance worker perspectives on the insertion of digitised drone technologies in the European steel industry. The industry is aiming for a 'business model transformation' by means of digitalisation, which includes the use of drone technologies for maintenance functions. In this paper, we explore on what basis might such workers embrace or resist this new technology. Drawing on data from a project investigating the use of drones for a 'safer, faster and leaner' workplace, we employ an analysis of technology 'effects' to discuss the risks and benefits to workers of drone technologies (see Orlikowski, Organ. Sci ., 3, 1992, 398; Edwards and Ramirez, New Technol. Work Employ ., 31, 2016, 99). The insertion and use of drone technology within the industry raises questions for the industry's highly skilled workers and their representatives on the 'effect' of drone innovations on the industry's existing structures and patterns of work.